Treatment outcomes for eosinophilic esophagitis in children with esophageal atresia. Issue 6 (15th April 2015) - Chan, L. J.; Tan, L.; Dhaliwal, J.; Briglia, F.; Clarkson, C.; Krishnan, U.
Summary: Eosinophilic esophagitis (EoE) has been reported to be more prevalent in patients with esophageal atresia/tracheoesophageal fistula (EA‐TEF). To date, there is limited data on the management of EoE in this group of patients. The aim of this study is to evaluate the treatment outcomes of EoE in children with EA‐TEF. A retrospective chart review was performed on all EA‐TEF children who were diagnosed with and treated for EoE between January 2000 and September 2013 at the Sydney Children's Hospital. Data collected included details of the patient's treatment, post‐treatment endoscopy, symptoms and nutrition. Twenty patients were included in the study. Median age at diagnosis was 26 months (8–103 months), and median time from diagnosis to last follow‐up was 23 months (2–132 months). Patients were treated with budesonide slurry, swallowed fluticasone, elimination diet alone or in combination. All patients were on proton pump inhibitors at time of diagnosis of EoE which was continued. Six out of seven patients who had furrowing/exudate in endoscopy at diagnosis had complete resolution at a median follow‐up period of 26 months ( P = 0.031). Median peak intraepithelial eosinophil count reduced significantly from 30/high‐powered field (HPF) (19–80/HPF) to 8/HPF (0–85/HPF) (median time for improvement = 24 months) ( P = 0.015). There was a significant reduction in symptoms of dysphagia and reflux post‐treatment ( P < 0.001). Prevalence of strictures significantly decreased ( P = 0.016), as did need for dilatations ( P = 0.004). In four out of six patients with gastrostomies at baseline, the feeding improved on treatment of EoE and the gastrostomy could be closed. There was also a nonsignificant trend towards improvement in weight and height 'z scores' of the patients. Treatment of EoE in children with EA‐TEF was found to significantly reduce intraepithelial eosinophil count, symptoms, strictures and need for dilatations.